Academic Audit Committee Directors, Tax Governance, and Corporate Tax Avoidance - Sintia Nurlitasari; Umatun Markhumah (Inovasi Analisis Data, 2025)
Purpose – This paper investigates the degree to which academic members of audit committees influence corporate tax avoidance via internal governance mechanisms. Design/methodology/approach – Structural equation modeling is applied in testing direct, mediating and antecedent governance relationships with findings reported. Findings – The results indicate that academic financial experts serving on audit committees are related to lower levels of corporate tax avoidance. This relationship is basically indirect and works through a higher quality of tax governance, consisting in better law, high control risk oversight and more transparency. The findings suggests that academic directors primarily act as effective monitors rather than advisers in the context of tax planning. Stronger tax governance, for its part, limits managerial discretion in tax decisions and discourages aggressive-taxing behavior. Moreover, the analysis also implies that governance-related mechanisms largely contribute to determine tax policies, especially in cases where inside monitoring is essential. Originality/value – We contribute to the tax avoidance literature by incorporating tax governance quality as an intervening factor between audit committee members with accounting expertise and tax outcomes. It contributes to the existing literature on board heterogeneity by emphasizing the unique contribution of academic directors in governance-sensitive areas such as taxation. Research Implications – The findings highlight the significance of expertisebased AC composition and have implications for regulating corporate tax behaviours towards more responsible and transparent governance.